A framework for teaching an undergraduate data analytics class. (26th April 2021) - Firth, David R.; Triche, Jason; Lucus, David J.
The explosive growth of data analytics has led to a large demand for analytical skills which is outstripping the supply of this skillset. Business schools across the world are responding to this challenge by offering graduate and undergraduate programs in data analytics. There is a growing body of literature covering the graduate level programs, but very little literature covers the undergraduate courses. This article covers the basic topics, themes and universal issues in teaching the undergraduate introduction to the data analytics course. We provide an over-arching framework on how to deliver an introduction course. We examine three different introduction classes at three AACSB accredited schools. We conclude with common issues, mitigation plans, and lessons learned.